2022
DOI: 10.1155/2022/2182783
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chitosan Microparticles Encapsulating Bacterial Cell-Free Supernatants and Indole Acetic Acid, and Their Effects on Germination and Seedling Growth in Tomato (Solanum lycopersicum)

Abstract: Encapsulation of biostimulant metabolites has gained popularity as it increases their shelf life and improves their absorption, being considered a good alternative for the manufacture of products that stimulate plant growth and fruit production. Cell-free supernatants (CFS) were obtained from nine indole-3-acetic acid (IAA) producing bacterial strains. Stenotrophomonas maltophilia (PT53T) produced the highest concentration of IAA (15.88 μg/mL) after 48 h of incubation. CFS from this strain, as well as an IAA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The application of phytohormones directly using nanoparticles for plant growth promotion and defense induction has been recently explored. Recent studies have combined nanocarriers with hormones like SA, GA, JA, ABA, and IAA for the promotion of plant growth properties ( Pereira et al., 2017 ; Clemente et al., 2018 ; Sun et al., 2018 ; Kumaraswamy et al., 2019 ; Korpayev et al., 2021 ; Gonzalez-Montfort et al., 2022 ; Wu et al., 2022 ). Future experiments that analyze the effect of nanoparticles on auxin production by endophytes and employ their use in the formulation of bioinoculants will be beneficial.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The application of phytohormones directly using nanoparticles for plant growth promotion and defense induction has been recently explored. Recent studies have combined nanocarriers with hormones like SA, GA, JA, ABA, and IAA for the promotion of plant growth properties ( Pereira et al., 2017 ; Clemente et al., 2018 ; Sun et al., 2018 ; Kumaraswamy et al., 2019 ; Korpayev et al., 2021 ; Gonzalez-Montfort et al., 2022 ; Wu et al., 2022 ). Future experiments that analyze the effect of nanoparticles on auxin production by endophytes and employ their use in the formulation of bioinoculants will be beneficial.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Several studies have shown that encapsulated SA generates pathogenic resistance against Fusarium verticillioides and Sclerotium rolfsii in maize and rice, respectively [ 213 , 214 ], and cold and salt tolerance in sunflower and grape [ 215 , 216 ], respectively. Treatments with encapsulated JA and ABA provide resistance against cold and drought stress in cherry tomato and Arabidopsis [ 217 , 218 ], respectively, and treatments with encapsulated IAA and GAs enhance plant growth and seed germination rates in tomato and bean [ 219 , 220 ]. Once the plant recognizes that it is under stress, signal transduction cascades are triggered and start a fluctuation between growth and stress response [ 94 ].…”
Section: Encapsulation Can Improve Phytohormone Biological Effects In...mentioning
confidence: 99%
“…cerasiforme (cherry tomato) • Used as coating to enhance cold time storage [ 218 ] • Coacervation • Alginate and chitosan • Solanum tuberosum (potato) • Tuber postharvest treatment for preserving [ 221 ] • Co-extrusion • PLGA • Vitis vinifera (grape) • Pest management [ 222 ] Abscisic acid • Sol–Gel encapsulation • Amorphous silica • Arabidopsis thaliana • Provides resistance against drought stress [ 217 ] • In-situ polymerization • Lignin • Oryza sativa (rice) and Arabidopsis thaliana • Increases drought resistance [ 223 ] Auxins • Ionic gelation • Chitosan • Solanum lycopersicum (tomato) • Increase germination and seedling growth rate. Acts as biostimulant [ 220 ] • Co-extrusion • Alginate and chitosan • Solanum lycopersicum (tomato) • Increase morphological characteristics [ 224 ] • Ionic gelation • Chitosan • Malus domestica (apple) • Promote adventitious rooting [ 225 ] Gibberellins • Ionic gelation • Chitosan • Phaseol...…”
Section: Encapsulation Can Improve Phytohormone Biological Effects In...mentioning
confidence: 99%